(untitled) (Herald of the National Children’s Medical Center, 2025)
Meningoencephalitis is an acute or subacute inflammation of the brain and its membranes, accompanied by pronounced clinical symptoms and a risk of poor prognosis. In children, infectious forms of encephalitis are often viral in nature; however, in a number of cases, the etiology remains undetermined, which complicates diagnosis and the choice of targeted treatment. The presented clinical case illustrates the challenges of diagnosing and managing patients with suspected meningoencephalitis of unclear etiology in early childhood.